Evolução da rotação de anãs brancas rápidas e magnéticas remanescentes de fusões de binárias de anãs brancas - Lacerda, Isabelle Assis (2024)
Within the population of white dwarfs, there is a group with unusual characteristics that challenge the single-star evolution model to explain their origin. These white dwarfs are massive, highly magnetic, and rapidly rotating, with masses that approach the Chan-drasekhar limit, magnetic field strengths between 106 G and 109 G and rotation periods ranging from minutes to seconds. One proposed formation process for these objects is the coalescence of a binary white dwarf system, where the conservation of mass, angular momentum, and magnetic flux can account for their particular parameters. This thesis studies the rotational evolution of the rapidly rotating, massive, and magnetic white dwarf RE J0317-853 (EUVE J0317-85.5), based on the assumption that it originated from the merger of a double degenerate system. For our investigation, we adopted the modeling developed by Sousa et al. (2022). In the post-merger context, the white dwarf is surrounded by a debris disk, with the presence of a matter flow towards the star. We calculated that the rotation of the white dwarf goes through three distinct phases, linked to the torques acting on it, spending most of its life undergoing magnetic braking. For an accretion rate of M˙ = 1.13 × 10−7 M⊙/year and a disk mass of Md = 0.31 M⊙, RE J0317-853 can reach the observed period of 725.7 s in approximately 0.2 Gyr. We estimated two possible configurations for the progenitor system of this white dwarf based on the mass ratio between the progenitors. RE J0317-853 could be the product of the merger of a white dwarf system with masses of 1.00 M⊙ and 0.50 M⊙, or it could have been formed by the coalescence of progenitors with masses of 0.75 M⊙ and 0.74 M⊙. The results obtained in this study resemble those of Sousa et al. (2022) for the progenitors of the white dwarf J2211+1136 (0,98 M⊙ and 0,49 M⊙), which, in turn, are similar to the configuration of the known double degenerate system NLTT 12758 (0,83 M⊙ and 0,69 M⊙), studied by Kawka et al. (2016). Another binary system composed of white dwarfs with masses similar to our estimates is the system NLTT 44447, formed by the magnetic white dwarf with 0.94 M⊙ and its non-magnetic companion, with 0.54 M⊙ (KAWKA et al., 2016). However, this system lacks measurements of the orbital period and rotational period of the stars. Future measurements of these parameters would allow a better assessment of the similarity between our estimate and this system, indicating whether this binary system could undergo coalescence